Pelatihan Keamanan Digital untuk Meningkatkan Cyber Security Awareness bagi Masyarakat di Kelurahan Bontonompo Kabupaten Gowa - Ruslan, Andi; Aris, Valentino; Taufik, Muhammad; Hamzah, Qardawi; Asmirani, Sri (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to enhance digital security literacy among local government staff and residents of Bontonompo Village, Gowa Regency. The program was conducted using lectures, discussions, hands-on practice, and evaluation through pre-tests and post-tests to assess participants’ knowledge improvement. A total of 30 participants actively joined the training, consisting of village staff and community members. The evaluation results revealed a significant increase in the average score from 55 to 82, indicating improved understanding of phishing detection, personal data protection, and identification of fake information. The training proved effective in raising awareness and basic digital security skills among participants. This activity is expected to serve as an initial step in strengthening a secure and sustainable digital ecosystem within Bontonompo Village.